Accuracy of shock index versus ABC score to predict need for massive transfusion in trauma patients. Issue 1 (January 2018) - Schroll, Rebecca; Swift, David; Tatum, Danielle; Couch, Stuart; Heaney, Jiselle B.; Llado-Farrulla, Monica; Zucker, Shana; Gill, Frances; Brown, Griffin; Buffin, Nicholas; Duchesne, Juan
Abstract: Background: Various scoring systems have been developed to predict need for massive transfusion in traumatically injured patients. Assessments of Blood Consumption (ABC) score and Shock Index (SI) have been shown to be reliable predictors for Massive Transfusion Protocol (MTP) activation. However, no study has directly compared these two scoring systems to determine which is a better predictor for MTP activation. The primary objective was to determine whether ABC or SI better predicted the need for MTP in adult trauma patients with severe hemorrhage. Methods: This was a retrospective cohort study which included all injured patients who were trauma activations between January 1, 2009 and December 31, 2013 at an urban Level I trauma center. Patients <18 years old or with traumatic brain injury (TBI) were excluded. ABC and SI were calculated for each patient. MTP was defined as need for >10 units PRBC transfusion within 24 h of emergency department arrival. Sensitivity, specificity, and area under the receiver operating characteristic curve (AUROC) were used to evaluate scoring systems' ability to predict effective MTP utilization. Results: A total of 645 patients had complete data for analysis. Shock Index ≥1 had sensitivity of 67.7% (95% CI 49.5%–82.6%) and specificity of 81.3% (95% CI 78.0%–84.3%) for predicting MTP, and ABC score ≥2 had sensitivity of 47.0% (95% CI 29.8%–64.9%) and specificity of 89.8% (95% CI 87.2%–92.1%). AUROC analyses showed SI to be the strongest predictor followed by ABC score with AUROC values of 0.83 and 0.74, respectively. SI had a significantly greater sensitivity (P = 0.035), but a significantly weaker specificity (P < 0.001) compared to ABC score. Conclusion: ABC score and Shock Index can both be used to predict need for massive transfusion in trauma patients, however SI is more sensitive and requires less technical skill than ABC score.